Study of heterosis in heat tolerant tomato (Solanum lycopersicum) during summer (Bangladesh Journal of Agricultural Research, 2013)
An experiment was conducted at the Vegetable Research Field of Olericulture Division, Horticulture Research Cente, Bangladesh Agricultural Research Institute (BARI), Gazipur during May to October 2008 to study heterosis using eight parents viz., P1, P2, P3, P4, P5, P6, P7, and P8. Most of the combinations showed better parent heterosis for earliness. Eight crosses showed positive heterosis for flower production. The highest heterotic effect for fruit set (%) was found in the cross P6 × P7 (62.59%) followed by that in P7 × P8 (60.49%) and P1 × P7 (40.00%). For fruits per plant, 8 crosses provided more than 15 % heterosis over better parent. Considering fruit yield per plant, higher degree of heterosis was manifested by 24 hybrids over better parent ranging from 13.58 to 282.63 %. Cross combination P4 x P7 showed the maximum significant positive heterosis followed by P6 x P7 (187.84 %), P4 x P8 (166.97 %), P3 x P7 (146.08 %), P3 xP6 (103.92 %), and P1 X P7 (100.45 %) and the minimum in P4 x P6 (13.58 %). For viable pollens, P3 x P5 (20.56 %) exhibited the highest positive heterosis. In case of shelf life, the highest heterosis was observed by the cross P3 x P6 (22.78 %) followed by that in P4 x P6 (22.29 %) and P2 x P6 (14.40 %). For fruit flesh thickness, 12 hybrids exhibited more than 10 % heterosis. Pollen tubes as well as viable pollens showed positive correlation with fruit set. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16980 Bangladesh J. Agril. Res. 38(3): 531-544, September 2013